Method for preparing carbon nanotubes from natural rubber

By thermally decomposing natural rubber and contacting it with catalyst for heat treatment, the problem of synthesis of carbon nanotubes in the prior art relying on fossil fuels is solved, efficient and sustainable carbon nanotube synthesis is achieved, and the characteristics of nanotubes can be adjusted.

CN111465579BActive Publication Date: 2025-02-11AGENCY FOR SCI TECH & RES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201880068455.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-09-27
Filing Date
2018-09-27
Publication Date
2025-02-11
Estimated Expiration
2038-09-27

AI Technical Summary

Technical Problem

Synthetic carbon nanotubes in the prior art rely on fossil fuels, resulting in limited resources and unsustainable.

Method used

Carbon nanotubes are formed by thermally decomposing natural rubber as the first material and contacting with the catalyst for heat treatment. The method includes thermally decomposing the natural rubber at a first temperature, and then contacting the catalyst at a second temperature for heat treatment to form the carbon nanotubes.

Benefits of technology

The efficient synthesis of carbon nanotubes from natural rubber is achieved, and the diameter and wall thickness of the nanotubes can be adjusted by adjusting the synthesis conditions, providing a sustainable synthesis method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111465579B_ABST
    Figure CN111465579B_ABST
Patent Text Reader

Abstract

A method for synthesizing carbon nanotubes from natural rubber, comprising: providing a first material, which may include natural rubber or a derivative thereof, thermally decomposing the first material into an intermediate material at a first temperature, contacting the intermediate material with a catalyst, and thermally treating the intermediate material in contact with the catalyst at a second temperature to form carbon nanotubes. Adjusting the average properties of the resulting nanotubes comprises performing the synthesis method as a reference method, and in order to reduce the average diameter of the nanotubes: reducing the second temperature and / or reducing the reaction time and / or increasing the H2 concentration in the forming gas relative to the reference method. Alternatively, in order to increase the average diameter of the nanotubes: increasing the second temperature and / or increasing the reaction time and / or reducing the H2 concentration in the forming gas relative to the reference method.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority from Singapore Application No. 10201707943S filed on September 27, 2017, which is incorporated herein by reference in its entirety for all purposes. Technical Field

[0003] Various aspects of the present disclosure may be directed to a method of synthesizing carbon nanotubes from natural rubber. Various aspects of the present disclosure may be directed to methods of adjusting average properties of the resulting nanotubes produced by the synthesis method. Background Art

[0004] One-dimensional carbon nanomaterials have important industrial applications due to their unique mechanical and physical properties. For example, carbon nanofibers are widely used in aerospace, high-end sports and industrial products. Carbon nanotubes (CNTs) are another one-dimensional carbon nanomaterial that is stronger, lighter and more conductive than carbon nanofibers. CNTs have broader applications, such as transparent electrodes as basic components of organic solar cells, as Li-ion battery electrodes, supercapacitors, field effect transistors and catalysts. In 2011, the global market for various CNT grades was $192 million. By 2016, the estimated revenue was $527 million. In 2016, China's production volume was about 3,000 metric tons. Currently, the conventional way to synthesize CNTs is by thermal decomposition of fossil fuels on active metal catalysts, mainly gaseous hydrocarbons (CH4, C2H4, C2H2, etc.). However, the use of fossil fuels to synthesize CNTs is unsustainable because it relies on limited resources. SUMMARY OF THE INVENTION

[0006] Various embodiments may provide a method for synthesizing carbon nanotubes from natural rubber, also referred to hereinafter as a synthesis method. The method may include providing a first material, which may include natural rubber or a derivative thereof. The method may further include thermally decomposing the first material into an intermediate material at a first temperature. The method may further include contacting the intermediate material with a catalyst. The method may further include thermally treating the intermediate material in contact with the catalyst at a second temperature to form carbon nanotubes.

[0007] Various embodiments may provide a method for adjusting the average properties of the resulting nanotubes produced by the synthesis method. The method may include performing the synthesis method as a reference method, and for reducing the average diameter of the nanotubes, the method may include reducing the second temperature and / or reducing the reaction time and / or increasing the H2 concentration in the formation gas relative to the reference method. Alternatively, the method may include performing the synthesis method as a reference method, and for increasing the average diameter of the nanotubes, the method may include increasing the second temperature and / or increasing the reaction time and / or reducing the H2 concentration in the formation gas relative to the reference method. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The invention will be better understood with reference to the detailed description when considered in conjunction with the non-limiting examples and accompanying drawings, in which:

[0010] Figure 1 shows a schematic diagram of a method 100 for carbon nanotube synthesis according to various embodiments;

[0011] Figure 2 shows a schematic diagram of a process 200 for forming a catalyst according to various embodiments;

[0012] Figure 3 A schematic diagram of an exemplary reactor 300 for performing at least one of: decomposing a first material, thermally treating the first material, calcining a catalyst precursor, reducing a catalyst precursor is shown according to various embodiments.

[0013] Figure 4 shows a graph 400 with thermogravimetric analysis (TGA) results of natural rubber;

[0014] Figure 5 X-ray diffraction (XRD) patterns of various catalyst samples in bulk form and after different reduction times and temperatures are shown according to various embodiments.

[0015] Figure 6 Transmission electron microscope (TEM) images of various catalyst samples reduced at different temperatures according to various embodiments are shown.

[0016] Figure 7 Transmission electron microscopy (TEM) images of various catalyst samples after different reduction times according to various embodiments are shown.

[0017] Figure 8 Shown are a scanning electron microscope (SEM) image and a TEM image of the CNT obtained in the first example according to various embodiments.

[0018] Fig. 9Shown are a scanning electron microscope (SEM) image and a TEM image of CNTs obtained in the second example according to various embodiments.

[0019] Fig.10 Shown are a scanning electron microscope (SEM) image and a TEM image of CNTs obtained in the third example according to various embodiments.

[0020] Detailed Description

[0021] The following detailed description refers to the accompanying drawings, which illustrate the specific details and embodiments of the present invention in a diagrammatic manner. These embodiments have been described in sufficient detail to enable those skilled in the art to implement the present invention. Other embodiments may be utilized without departing from the scope of the present invention, and structural and logical changes may be made. Various embodiments are not necessarily mutually exclusive, because some embodiments may be combined with one or more other embodiments to form new embodiments.

[0022] Features described in the context of one embodiment may be correspondingly applicable to the same or similar features in other embodiments. Features described in the context of one embodiment may be correspondingly applicable to other embodiments, even if not explicitly described in these other embodiments. In addition, additions and / or combinations and / or substitutions described for features in the context of an embodiment may be correspondingly applicable to the same or similar features in other embodiments.

[0023] In the context of various embodiments, the articles “a,” “an,” and “the” used with respect to features or elements include reference to one or more of the features or elements.

[0024] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0025] Various aspects of the invention may relate to methods for synthesizing carbon nanotubes directly from solid natural rubber (including gels, such as sol-gels), or solution preparation of catalysts (such as transition metal catalysts), and two-stage processes for rubber decomposition and CNT growth, respectively. Natural rubber or waste of natural rubber can be used as a carbon source to form CNTs.

[0026] As used herein and according to various embodiments, the term "about" in relation to given values ​​(eg, temperature and time period) is intended to include values ​​within a range of + / - 10% of, and inclusive of, the particular given value.

[0027] As used herein and according to various embodiments, the term "substantially" and its derivatives are defined as at least 10% by weight, preferably at least 30% by weight, and further preferably at least 50% by weight of the total weight. For example, "substantially comprising natural rubber" may mean that at least 10% by weight, preferably at least 30% by weight, and further preferably at least 50% by weight of the total weight is natural rubber.

[0028] According to various embodiments, the first material may substantially include natural rubber or its derivatives or be composed of natural rubber or its derivatives. In various embodiments, natural rubber may refer to latex obtained from plants (preferably trees) and obtained from the processing stage before adding sulfur. Therefore, according to various embodiments, natural rubber can be obtained from the processing step of natural latex between collecting natural latex (for example, from trees) and adding sulfur (for example, before the vulcanization step). For example, latex can be coagulated latex. Natural rubber may also refer to natural rubber latex, preferably derived from Hevea brasiliensis. In various embodiments, the water concentration in natural rubber or its derivatives may be less than 1 weight %. In various embodiments, the first material may include vulcanized rubber less than 10 weight %. In various embodiments, the water concentration of the first material may be less than 1 weight %. For example, the material comprising natural rubber may be dried before being provided as the first material. The first material may be the waste obtained from the processing of natural rubber, or simply referred to as "natural rubber waste", for example, may be selected from: latex, coagulated latex. In one example, the natural rubber or its derivatives may be selected from one or more of the following: latex, coagulated latex, natural rubber waste, recycled rubber (from natural rubber) treated to remove sulfur.

[0029] The main component of natural rubber is polyisoprene, along with small amounts of impurities such as proteins, natural lipids, and inorganic compounds. Polyisoprene consists of long chains of repeating isoprene molecules. The molar mass of polyisoprene in rubber is from about 50,000 to about 3,000,000 g / mol. Natural rubber can be distinguished from synthetic rubber because synthetic rubber has a higher decomposition temperature.

[0030] According to various embodiments, the natural rubber derivative may be recycled rubber. The recycled rubber may be rubber that has been treated so that sulfur is removed, for example, the method may include treating the rubber to remove sulfur so as to reduce the amount of sulfur.

[0031] Figure 1A schematic diagram of a method 100 for synthesizing carbon nanotubes according to various embodiments is shown. In step 102, a first material may be provided. The first material may include natural rubber or a derivative thereof. In a further step 104, the first material may be thermally decomposed at a first temperature into an intermediate material. The intermediate material may be volatile and may be transported by a gas stream. In a further step 106, the intermediate material may be contacted with a catalyst, and in step 108, the intermediate material in contact with the catalyst may be thermally treated at a second temperature, thereby forming carbon nanotubes. Steps 106 and 108 may be performed simultaneously.

[0032] According to various embodiments, thermally decomposing the first material can be performed at a first location. The first location can be in a first furnace, for example, the first location can be a first section of the first furnace.

[0033] According to various embodiments, thermally decomposing the first material into an intermediate material is performed at a first temperature that can be selected from about 200°C to about 500°C, such as about 250°C to about 450°C, and further such as about 350°C to about 420°C.

[0034] According to various embodiments, heat treating the intermediate material may be performed at a second location. The second location may be different from the first location. The second location may be selected from: a second furnace, or a second section of a first furnace. For example, the first location may be a first section of a first furnace, and the second location may be a second section of the first furnace.

[0035] According to various embodiments, the time during the heat treatment of the intermediate material in contact with the catalyst may also be referred to as the reaction time. For example, the reaction time may last from about 10 minutes to about 2 hours, and further for example from about 10 minutes to about 50 minutes.

[0036] According to various embodiments, heat treating the intermediate material may be performed at a second temperature, such as in contact with a catalyst. The second temperature may be selected from about 600°C to about 800°C, such as about 650°C to about 800°C.

[0037] According to various embodiments, at least one of the following is performed under a forming gas: (i) thermally decomposing the first material and (ii) thermally treating the intermediate material. The forming gas can be provided as a gas stream. The forming gas can be an inert gas, such as nitrogen (N2) or argon.

[0038] The term "inert gas" should be interpreted broadly to include any gas that does not form chemical bonds when used for chemical vapor deposition. Exemplary inert gases include rare gases, but may include other gases as long as they do not form chemical bonds.

[0039] According to various embodiments, the gas flow can be from a first location to a second location, and the intermediate material can be carried by the gas flow from the first location to the second location. For example, the forming gas can transport the intermediate material from the first location to the second location, so that after the first material is decomposed, the intermediate material can be thermally treated at the second location. Thermal decomposition of the solid rubber produces volatile oils and / or gases, for example, the volatile oil can include 4 to 7 isoprene units.

[0040] During the thermal treatment of the intermediate material in contact with the catalyst at the second temperature, carbon nanotubes are formed. According to various embodiments, the method may further include separating the carbon nanotubes from any remaining residues of the reaction.

[0041] Figure 2 A schematic diagram of a process 200 for forming a catalyst according to various embodiments is shown, which method may be included in the synthesis method. In process step 202, the catalyst may be provided in the form of a gel (e.g., sol-gel) or a solution. A further process step 204 may include drying the gel or solution to obtain a dry material. Optionally, the dry material may be ground. A further process step 206 may include calcining the catalyst precursor, in other words, calcining the dry material or ground dry material. A further process step 208 may include reducing the catalyst precursor to form a catalyst.

[0042] According to various embodiments, the catalyst may be provided as a catalyst precursor, for example, at a second location, and may be further converted into a catalyst, for example, at a second location. Converting the catalyst precursor into the catalyst may include the following method steps: calcining the dried material to obtain a calcined material and reducing the calcined material, and this conversion step may be performed, for example, at a second location. Thus, the catalyst precursor may be provided and converted at a second location within the reactor without the need for transport between different locations, thereby simplifying the process.

[0043] According to various embodiments, the method may further include forming the catalyst, wherein forming the catalyst may include forming a gel (e.g., using a sol-gel process) or a solution. Thus, in at least one forming step, the catalyst precursor may be provided in gel form, such as in the form of a dried and ground gel.

[0044] According to various embodiments, at least a first component and a complexing agent may be used to form the gel or solution. For example, the first component may be provided in the form of a first component nitrate. The first component may be a transition metal or a mixed metal, which may be selected from: a transition metal, a noble metal, for example, selected from at least one of the following: Ni, Fe, Co. The first component nitrate may be selected from at least one of the following: a nitrate of Ni, a nitrate of Fe, a nitrate of Co.

[0045] According to various embodiments, the complexing agent may be citric acid or another suitable agent.

[0046] In some embodiments, for example, in addition to the first component and the complexing agent, at least a second component in the form of a nitrate of the second component may be used to form the gel or solution. The second component may be selected from Al, Si, Mg, L, La, and combinations thereof. As used herein and according to various embodiments, "L" may represent an element or combination of elements selected from the lanthanide series. An example of L is lanthanum (La).

[0047] According to various embodiments, the first component and the second component are reacted together to form a catalyst precursor.

[0048] According to various embodiments, the second component may be converted into an oxide, for example during calcination. The oxide may be selected from at least one of the following: Al2O3, SiO2, MgO, La2O3. These oxides may serve as a support in the catalyst.

[0049] According to various embodiments, the method may further include drying (to obtain a dried material), optionally grinding, and calcining the gel or solution to obtain a calcined material. The method may further include reducing the calcined material to release the components in the elemental state as particles, such as metal particles, to form a catalyst. In some embodiments, at least one of drying, calcining, and reducing can be performed at a second location without removing the catalyst before using it to form carbon nanotubes.

[0050] According to various embodiments, the drying temperature employed during drying may be selected from about 60°C to about 120°C.

[0051] According to various embodiments, the calcination temperature employed during calcination may be selected from about 500° C. to about 800° C. The calcination step may be performed in a gas comprising oxygen, such as a gas comprising or consisting of air.

[0052] According to various embodiments, the reduction step may be performed in the presence of hydrogen, for example, using a flow of an inert gas mixed with H 2 . An example of an inert gas is N 2 .

[0053] According to various embodiments, the temperature during the reducing step may be selected from about 650°C to about 800°C.

[0054] According to various embodiments, the catalyst may include particles of a single metal and / or mixed metals, which may be selected from: transition metals, noble metals, such as Ni or FeNi particles. The catalyst may be provided in the form of catalyst particles, for example, including more than one metal type, for example selected from: transition metals, noble metals. The catalyst may include a carrier, such as aluminum oxide, such as Al2O3.

[0055] As used herein and according to various embodiments, temperature can refer to the temperature measured at the material (preferably solid or liquid) being processed. For example, the drying temperature of natural rubber can refer to the temperature measured at the dried natural rubber. For example, the calcination temperature of a gel or solution can refer to the temperature measured at the calcined dry material. For example, the temperature of the reduction step of the catalyst can refer to the temperature measured at the reduced catalyst precursor. For example, the second temperature (also referred to as the formation temperature) can refer to the temperature measured at the catalyst when forming carbon nanotubes. For example, the temperature of the decomposition step of natural rubber can refer to the temperature measured at the decomposed natural rubber.

[0056] According to various embodiments, the various method steps of any of the described methods may be performed at ambient pressure, for example at about 101325 Pa.

[0057] According to various embodiments, the spent catalyst may be recycled for the production of fresh catalyst.Thus, methods according to various embodiments may include recycling spent catalyst for the production of fresh catalyst.

[0058] The synthesis method can be easily adapted to tune the properties of the resulting nanotubes, for example to obtain nanotubes with a certain diameter.

[0059] Various embodiments may provide a method for adjusting the average properties of the resulting nanotubes produced by the synthesis method. The method may include performing the synthesis method as a reference method, with a second temperature as a reference second temperature, a reference reaction time, and a reference concentration of H2 in the forming gas, thereby producing carbon nanotubes comprising a reference average diameter. The method may further include adjusting at least one of: adjusting the second temperature to an adjusted second temperature, adjusting the reaction time to an adjusted reaction time, and adjusting the H2 concentration in the forming gas to an adjusted concentration, thereby providing adjusted synthesis parameters. The method may further include performing the synthesis method with the adjusted synthesis parameters, thereby producing carbon nanotubes having an adjusted average diameter.

[0060] In some embodiments, at least one of the following may be provided to prepare carbon nanotubes having an adjusted average diameter smaller than a reference average diameter: the adjusted second temperature is lower than the reference second temperature; the adjusted reaction time is shorter than the reference reaction time; the adjusted concentration is greater than the reference concentration. Alternatively, in some embodiments, at least one of the following may be provided to prepare carbon nanotubes having an adjusted average diameter larger than the reference average diameter: the adjusted second temperature is higher than the reference second temperature; the adjusted reaction time is longer than the reference reaction time; the adjusted concentration is less than the reference concentration.

[0061] Figure 3A schematic diagram of an exemplary reactor 300 for performing at least one of: decomposing a first material, thermally treating the first material, calcining a catalyst precursor, reducing a catalyst precursor is shown according to various embodiments. Figure 3 A reactor 300 is shown that includes a first location 322 in which a first material can be provided, such as in a quartz reactor tube, and a second location 332 in which a catalyst can be provided or a catalyst precursor can be provided and converted to a catalyst, such as in a quartz reactor tube. For illustration purposes, Figure 3 In the example shown, the first location 322 is shown included in the first furnace 320 and the second location 332 is shown included in the second furnace 330. Alternatively, the second location may be located in the first furnace, and for example, the first material and the catalyst may be included in the same quartz reactor tube, and the second furnace may not be required. Figure 3 Also shown is a flow path 304 for a gas 302 (eg, forming gas) that may flow from a first location 322 to a second location 332 .

[0062] Experimental Results

[0063] Use as Figure 3 The experiment was carried out in the reactor shown. The quartz reactor tube was heated separately with an electric furnace, and the temperature was fully controlled and monitored. The catalyst was first reduced with a nitrogen / hydrogen flow in the upper furnace and then used for the catalytic reaction. The decomposition of the rubber was carried out in the lower furnace, and a nitrogen flow was introduced from the bottom of the reactor. Therefore, after the introduction of the first material and the catalyst precursor, the catalyst precursor can be converted into a catalyst, and nanotubes can be synthesized without opening the reactor.

[0064] Rubber decomposition

[0065] Figure 4 A graph 400 is shown with the results of a thermogravimetric analysis (TGA) of natural rubber. Horizontal axis 402 represents temperature in degrees Celsius. Graph 410 shows the weight loss of the sample, represented on axis 412. Graph 420 shows the derivative of graph 410, represented on axis 422. Graph 430 shows heat flow, represented on axis 432.

[0066] TGA results ( Figure 4 ) shows that natural rubber starts to decompose at 200°C and completes decomposition at 450°C, with less than 2 wt% remaining. A weight loss peak is observed between 350-450°C, indicating that rubber decomposition is a one-stage reaction. As shown, thermal decomposition is a suitable way to degrade solid polyisoprene into small molecules because it is simple and does not require complex procedures and expensive equipment. Therefore, any natural rubber containing polyisoprene can be used to produce carbon nanotubes.

[0067] Catalyst preparation

[0068] As mentioned above, Ni-Al2O3 catalyst is prepared by citric acid complexation, wherein Ni loading is greater than 5mol% to 30mol%. Typically, nickel nitrate (II) hexahydrate (11.6g, 0.04mol), aluminum nitrate monohydrate (67.0g, 0.18mol) and citric acid (46.0g, 0.24mol) are dissolved in 200mL deionized water. The solution is placed in an oven and maintained at 85°C until a viscous gel is formed. The oven temperature is then raised to 130°C and heated until completely dry. The dried mixture is carefully ground and calcined at 400°C for 1h, then at 700°C for 5h, using a heating rate of 1.5°C / min.

[0069] Figure 5 X-ray diffraction (XRD) patterns of various bulk catalyst samples are shown. Figure 5 (A) shows the XRD patterns of the bulk catalyst before reduction (catalyst precursor) (curve 511), after reduction at 600°C (curve 512), after reduction at 650°C (curve 513), after reduction at 700°C (curve 514), after reduction at 750°C (curve 515), and after reduction at 800°C (curve 516). Figure 5 The curves in (A) are offset vertically to enhance visualization. Figure 5 (B) shows XRD patterns of bulk catalyst at different times during reduction. Curve 521 shows the XRD pattern of bulk catalyst (catalyst precursor) before reduction, curve 522 after 0.5 h, curve 523 after 1 h, and curve 524 after 2 h.

[0070] XRD spectrum reveals the structural information of bulk catalyst after reduction. After calcination of catalyst, NiAl2O4 (spinel) phase is first formed in air treatment. During hydrogen reduction, Ni element can be reduced and separated from NiAl2O4 phase, thereby forming Ni nanoparticles on Al2O3 / NiAl2O4 surface. These newly formed Ni nanoparticles are the active ingredients of CNT growth. In XRD spectrum, three main peaks at 44.4°, 51.5° and 76° can be attributed to metal Ni. Peak intensity becomes higher with the increase of reduction temperature and time, indicating that more Ni is separated from NiAl2O4 phase. In addition, the half-height full width of peak narrows, which means that Ni particle size increases under high temperature or longer reduction time. Generally, average Ni particle size increases with the increase of reduction temperature or reduction time. For the growth of CNT with a small amount of amorphous carbon balls, suitable catalysts can have a particle size of about 7nm.

[0071] The same samples were characterized by TEM. The TEM images of Ni-based catalysts with various reduction temperatures and reduction times are shown in Figure 6 and 7 middle. Figure 6 Sample A reduced at 600°C, sample B reduced at 650°C, sample C reduced at 700°C, sample D reduced at 750°C, and sample E reduced at 800°C are shown. Figure 6 These samples correspond to Figure 5 (A) XRD pattern of.

[0072] Figure 7 Shown are sample A after 0.5 hour reduction time, sample B after 1 hour reduction time, and sample C after 1.5 hour reduction time. Figure 7 These samples correspond to Figure 5 (B) XRD pattern of.

[0073] The white dots indicate the presence of Ni active particles, and the gray large particles are Al2O3 or N1Al2O4 matrix. These TEM images show that within each sample, the size of the Ni particles is relatively uniform. Similar to the XRD results, there is a general trend of increasing particle size with increasing temperature or longer reduction time.

[0074] Growth of carbon nanotubes

[0075] The conversion of rubber to carbon nanotubes and the yield of carbon nanotubes per gram of catalyst were measured using excess catalyst. The experimental results show that, for example, about 40% to about 60% of the rubber can be converted into multi-walled carbon nanotubes. The I calculated from the Raman spectra G / I D (I G is the Raman signal intensity of the G band, I D The Raman signal intensity of the D band) values ​​are similar to those of carbon nanotubes grown from petroleum precursors, indicating that the CNTs are of similar quality with few defects.

[0076] Hereinafter, 3 examples of CNT growth using natural rubber as a first material according to various embodiments will be described.

[0077] Example 1: 1 g of dry natural rubber is provided as the first material in the first position. 0.5 g of a dried, ground and calcined catalyst (calcined material) is provided in the second position. The calcined material is prepared as described above. The catalyst is formed by reduction at a temperature of 775°C for 1 hour under a N2 / H2 flow (20:10 mL / min). After the catalyst is formed, the first material is thermally decomposed at a first temperature of 400°C into an intermediate material, which is transported to the second position to contact the catalyst. The intermediate material is heat-treated at a second temperature of 700°C for 1 hour under a N2 / H2 flow (20:10 mL / min). 0.20 g of multi-walled carbon nanotubes are obtained. The average outer diameter of the produced carbon nanotubes is 20.9 nm and the wall thickness is about 7.7 nm. A typical image of the obtained carbon nanotubes is shown in Figure 8 (A) SEM image of Figure 8 (B) TEM image.

[0078] Example 2: A second experiment was conducted as in Example 1, except that the second temperature was 750°C for 1 hour under a N2 flow (20 mL / min). 0.15 g of multi-walled carbon nanotubes were obtained. The average outer diameter of the produced carbon nanotubes was 25.1 nm and the wall thickness was about 9.3 nm. A typical image of the obtained carbon nanotubes is shown in Fig. 9 (A) SEM image of Fig. 9 (B) TEM image.

[0079] Example 3: A third experiment was conducted as in Example 2, except that the second temperature was 700°C. 0.13 g of multi-walled carbon nanotubes were obtained. The average outer diameter of the produced carbon nanotubes was 25.6 nm and the wall thickness was about 7.7 nm. A typical image of the obtained carbon nanotubes is shown in Fig.10 (A) SEM image of Fig.10 (B) TEM image.

[0080] Using the synthesis method according to various embodiments, natural rubber or its derivatives can be thermally decomposed at high temperature and then reconstructed on a metal-based catalyst to form carbon nanotubes. It is shown that high yields, such as 40-60%, of rubber can be converted into multi-walled carbon nanotubes with a narrow diameter distribution. The diameter and wall thickness of the carbon nanotubes can be adjusted by changing the synthesis conditions.

Claims

1. A method for synthesizing carbon nanotubes from natural rubber, comprising: - providing a first material comprising natural rubber or a derivative thereof; - thermally decomposing the first material into an intermediate material at a first temperature, wherein the first temperature is selected from 200° C. to 500° C.; - contacting the intermediate material with a catalyst, said catalyst being particles of a single metal and / or a mixture of metals selected from transition metals and noble metals; and - thermally treating the intermediate material in contact with the catalyst at a second temperature to form carbon nanotubes.

2. The method of claim 1, wherein the step of thermally decomposing the first material is performed in a first location, and wherein the first location is in a first furnace or in a section of the first furnace.

3. The method of claim 2, wherein the step of heat treating the intermediate material is performed in a second location, and wherein the second location is selected from: a second furnace or a second section of the first furnace.

4. The method of claim 3, wherein at least one of the steps of (i) thermally decomposing the first material and (ii) thermally treating the intermediate material is performed under a forming gas, wherein The forming gas is provided as a gas stream.

5. The method of claim 4, wherein the air flow is from the first location to the second location, thereby enabling the intermediate material to be transported from the first location to the second location.

6. The method according to claim 1 or 2, wherein the second temperature is selected from 600°C to 800°C.

7. The method according to claim 1 or 2, further comprising separating the carbon nanotubes from the remaining residue of the reaction.

8. The method of claim 3, wherein the catalyst is provided as a catalyst precursor in the second location and is converted to the catalyst in the second location.

9. The method of claim 1 or 2, further comprising recycling the spent catalyst to produce fresh catalyst.

10. The method of claim 1, further comprising forming a catalyst, wherein the method of forming the catalyst comprises forming a solution or a gel, optionally utilizing a sol-gel process.

11. The method of claim 10, wherein at least a first component and a complexing agent are used to form the solution or gel, the first component being in the form of a first component nitrate salt.

12. The method according to claim 11, wherein the first component is a transition metal, a noble metal, or a mixed metal thereof.

13. The method according to claim 11, wherein the first component is selected from at least one of the following: Ni, Fe, Co.

14. The method of claim 11, wherein at least a second component is used to form the solution or gel, the second component being in the form of a second component nitrate salt.

15. The method of claim 14, wherein the second component is selected from the group consisting of: Al, Si, Mg, La, and combinations thereof.

16. The method according to claim 11, further comprising drying, optionally grinding, and calcining the solution or gel to obtain a calcined material; and The calcined material is reduced to release the first component in a simple state as particles.

17. The method according to claim 14, further comprising drying, optionally grinding, and calcining the solution or gel to obtain a calcined material; and reducing the calcined material so as to release the first component in a simple state as particles, wherein the second component is converted into an oxide during calcination, and wherein the oxide is selected from at least one of the following: Al2O3, SiO2, MgO, La2O3.

18. The method according to claim 16 or 17, wherein the drying temperature adopted during drying is selected from 60°C to 120°C.

19. The method according to claim 16 or 17, wherein the calcination temperature employed during the calcination is selected from 500°C to 800°C.

20. The method of claim 16 or 17, wherein the reducing step is performed in the presence of hydrogen.

21. The method of claim 16 or 17, wherein the temperature during the reduction step is from 650°C to 800°C.

22. The method of claim 1 or 2, wherein the first material comprises less than 10% by weight of vulcanized rubber, optionally wherein the natural rubber is at least one of: latex, coagulated latex.

23. The method of claim 1 or 2, wherein the natural rubber derivative is recycled rubber, and wherein the recycled rubber is treated to remove sulfur.

24. The method of claim 1 or 2, wherein the first material is rubber waste obtained from natural rubber processing.

25. A method for adjusting the average properties of the resulting carbon nanotubes produced by the method according to any one of claims 4 to 24, comprising carrying out the method as a reference method, thereby producing carbon nanotubes comprising a reference average diameter, and To reduce the average diameter of the carbon nanotubes: lower the second temperature and / or reduce the reaction time and / or increase the H2 concentration in the forming gas relative to the reference method; or To increase the average diameter of the carbon nanotubes: increase the second temperature and / or increase the reaction time and / or decrease the H2 concentration in the forming gas relative to the reference method.

Citation Information

Patent Citations

  • Method for synthesis of carbon nanostructure material by using organic material

    CN102491308A